2012
DOI: 10.1016/j.amjsurg.2012.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Patient education level affects functionality and long term mortality after major lower extremity amputation

Abstract: Background In this study, we examine the relationship between level of education of patients and five year mortality following major lower extremity amputation. Methods We retrospectively reviewed the records of all patients who underwent above- or below-knee amputation at the Nashville VA by the vascular surgery service between January 2000 and August 2006. Formal level of education of the study patients was recorded. Outcomes were compared between those patients who had completed high school and those who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Self-rated literacy could not explain these educational disparities. The association that we found between educational level and health is consistent with the findings in other studies [22-26]. An unexpected finding in our study was the relatively high educational level among people from non-British/English background.…”
Section: Discussionsupporting
confidence: 93%
“…Self-rated literacy could not explain these educational disparities. The association that we found between educational level and health is consistent with the findings in other studies [22-26]. An unexpected finding in our study was the relatively high educational level among people from non-British/English background.…”
Section: Discussionsupporting
confidence: 93%
“…Although we have not collected data in patients who were not offered amputation (because other surgical options were available, or patient refusal or co-morbidity was felt to preclude surgery), it seems likely that a different casemix accounts for some of these differences. Corey and colleagues found that age, number of comorbidities, ASA grade and poor educational attainment (as a surrogate for lower socio-economic status) were associated with a worse five-year outcome after amputation [20]. To improve the outcome of patients undergoing amputation, the VSGBI released a quality improvement framework in November 2010, with the aim of reducing the peri-operative mortality of major lower limb amputation to < 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Corey revealed that persons with lower education level have an increased mortality rate after amputation. 13 That may be as well put on the above statement because those with higher levels of education care for them more and may adopt a preventing style instead of presenting to medical services in late advanced disease stages.…”
Section: Discussionmentioning
confidence: 99%